Two-dimensional (2D) Transition Metal Carbides/Nitrides (MXenes) and Transition Metal Borides (MBenes) as Emerging Functional Materials for Electrochemical Detection of Food Contaminants - Karakas, Canan Yagmur; Ozoglu, Ozum; Yildirim, Sema Nur; Sagdic, Osman; Gurmen, Sebahattin; Dertli, Enes; Uzunoglu, Aytekin (ELSEVIER SCI LTD, 2026)
Food safety is a major global challenge, driven by population growth, industrial food production, and rising public health concerns. Contaminants such as pathogen microorganisms, heavy metals, pesticides, mycotoxins, and antibiotic residues require rapid, sensitive, and reliable detection strategies. Electrochemical biosensors have emerged as efficient alternatives to conventional analytical methods due to their simplicity, low cost, and suitability for real-time monitoring. Two-dimensional (2D) materials, particularly MXenes and MBenes, have shown great promise in enhancing sensor performance. MXenes, composed of 2D transition metal carbides, nitrides, or carbonitrides, exhibit tunable surface terminations and high electrical conductivity, whereas MBenes (2D transition metal borides) offer superior oxidation stability and chemical robustness. This review outlines recent advances in the synthesis, structural tailoring, and application of MXene- and MBene-based electrochemical (bio)sensors for food safety monitoring, emphasizing their advantages, limitations, and future perspectives for practical implementation.
Keywords: biosensors; 2-dimensional materials; MBenes; MXenes; food safety; TI3C2TX MXENE; APTASENSOR; SAXITOXIN; ETCHANT; IONS; Chemistry; Food Science & Technology; Nutrition & Dietetics